ЯНГИ ЎЗБЕКИСТОН ШАРОИТИДА ЎЗБЕК ТИЛИ ТАРАҚҚИЁТИНИНГ ҲУҚУҚИЙ АСОСЛАРИ - Курбониязов, Г.А. (SCIENCE and SOCIETY, 2024)
The article analyzes the social significance of the decrees dedicated to the development of the state language, increasing its influence, and measures to improve the language policy in our country.